PERANCANGAN SISTEM INFORMASI MANAJEMEN STOK PADA TB. CENTRAL BANGUN JAYA - Melisa Melisa; Amroni Amroni; Dwi Ayu Gusriyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Central Bangun Jaya is engaged in the sale of building materials. In processing every day inventory control records, its still manually, in order that mistakes frequently arise in pricing items when making income because of the huge variety of styles of merchandise being sold. Similarly, the store frequently does now not reduce stock at some point of a income transaction, ensuing in a difference between the real inventory and the manual recording stock. Because of the problem, this have a look at goals to provide a technique to the difficulties experienced through TB. Central Bangun Jaya. This machine uses programming language PHP, framework laravel, visual Studio Code, and also MySQL. where on this study the use of the waterfall method with the gadget testing approach the use of the Blackbox method and system modeling used, particularly use case diagrams, activity diagrams, and sophistication diagrams. it can be concluded from this studies, the machine created can facilitate the shop in processing inventory management statistics, in order that gadget customers can minimize errors in order to arise and may be predicted to resolve problems that exist in TB. Central Bangun Jaya.